2021
DOI: 10.1542/peds.2021-052286
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Antibodies in Breast Milk After Vaccination

Abstract: This is a prepublication version of an article that has undergone peer review and been accepted for publication but is not the final version of record. This paper may be cited using the DOI and date of access. This paper may contain information that has errors in facts, figures, and statements, and will be corrected in the final published version. The journal is providing an early version of this article to expedite access to this information. The American Academy of Pediatrics, the editors, and authors are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 46 publications
3
35
3
Order By: Relevance
“…We also observed a similar pattern of increase in anti-RBD IgG levels in milk after the 2nd dose and positive correlation of blood and milk IgG levels. These findings stand in line with previous publications ( 32 , 33 ) and strengthen our knowledge about the transport of milk IgG antibodies from the blood to the milk ( 34 ). In contrast, milk anti-RBD IgA levels measured 4-10 weeks after 2nd dose, were not significantly higher compared to their levels after the 1st dose.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also observed a similar pattern of increase in anti-RBD IgG levels in milk after the 2nd dose and positive correlation of blood and milk IgG levels. These findings stand in line with previous publications ( 32 , 33 ) and strengthen our knowledge about the transport of milk IgG antibodies from the blood to the milk ( 34 ). In contrast, milk anti-RBD IgA levels measured 4-10 weeks after 2nd dose, were not significantly higher compared to their levels after the 1st dose.…”
Section: Discussionsupporting
confidence: 93%
“…In our study IgA levels in milk were measured 4-10 weeks post 2nd dose and based on other publications we expect that milk IgA levels will be relatively lower at this stage in compared to 10-14 days after 2nd dose. These differences in the timing of measurements might explain the differences in our findings, compared to other studies ( 32 , 35 ). Although we did not measure maternal blood IgA, other studies have shown that blood and milk IgA levels correlate when measured 7-10 days after the 2nd dose ( 13 , 36 ).…”
Section: Discussioncontrasting
confidence: 85%
“…Ten out of the 12 participants who had no detectable anti-RBD IgA, had infants older than 5.5 months at the time of sample collection. These findings are different from other publications that showed positive correlation of milk IgA levels (measured 2 weeks after 2nd dose) and baby age (32) or another study that didn't show correlation between these antibodies titters in milk and infant age (10 days after 2nd dose) (35). In our study IgA levels in milk were measured 4-10 weeks post 2nd dose and based on other publications we expect that milk IgA levels will be relatively lower at this stage in compared to 10-14 days after 2nd dose.…”
Section: Discussioncontrasting
confidence: 99%
“…similar pattern of increase in anti-RBD IgG levels in milk after the 2nd dose and positive correlation of blood and milk IgG levels. These findings stand in line with previous publications (32,33) and strengthen our knowledge about the transport of milk IgG antibodies from the blood to the milk (34). In contrast, milk anti-RBD IgA levels measured 4-10 weeks after 2nd dose, were not significantly higher compared to their levels after the 1st dose.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation